Inhibitory mechanisms of two Uncaria tomentosa extracts affecting the Wnt-signaling pathway - Gurrola Díaz, Carmen Magdalena; García-López, Pedro Macedonio; Gulewicz, Krzysztof; Pilarski, Radoslaw; Dihlmann, Susanne (Phytomedicine, 2011)
Uncaria tomentosa (“uña de gato”; “cat's claw”), a woody vine native to the Amazon rainforest, is commonly used in South American traditional medicine to treat a broad spectrum of diseases. Although recent studies have reported anti-inflammatory and anti-proliferative properties of different alkaloids extracted from this plant, the underlying molecular mechanisms of these effects have not been elucidated yet. Our study investigates the inhibitory mechanisms of Uncaria tomentosa extracts on the Wnt-signaling pathway, a central regulator of development and tissue homoeostasis. A modified cell-based luciferase assay for screening inhibitors of the Wnt-pathway was used for analysis. Three cancer cell lines displaying different levels of aberrant Wnt-signaling activity were transfected with Wnt-signaling responsive Tcf-reporter plasmids and treated with increasing concentrations of two Uncaria tomentosa bark extracts. Wnt-signaling activity was assessed by luciferase activity and by expression of Wnt-responsive target genes. We show that both, an aqueous and an alkaloid-enriched extract specifically inhibit Wnt-signaling activity in HeLa, HCT116 and SW480 cancer cells resulting in reduced expression of the Wnt-target gene: c-Myc. The alkaloid-enriched extract (B/Srt) was found to be more effective than the aqueous extract (B/W37). The strongest effect was observed in SW480 cells, displaying the highest endogenous Wnt-signaling activity. Downregulation of Wnt-signaling by a dominant negative-TCF-4 variant in non-cancer cells rendered the cells insensitive towards treatment with B/Srt. B/Srt was less toxic in non-cancer cells than in cancer cells. Our data suggest that the broad spectrum of pharmacological action of Uncaria tomentosa involves inhibition of the Wnt-signaling pathway, downstream of beta-Catenin activity.
Available online 14 December 2010
Gesehen am 20.07.2022